Trastuzumab deruxtecan for the treatment of metastatic non-small cell lung cancer harboring HER2 non-exon 19/20 mutations: four case reports - Meng, Yan; Du, Yanping; Liu, Xiaolin; Huang, Jue; Chen, Hanhan; He, Chunxia (Frontiers in Immunology, 2025)
BackgroundPatients with human epidermal growth factor receptor 2 (HER2)-mutant non-small cell lung cancer (NSCLC) have poor prognosis. Trastuzumab deruxtecan (T-DXd) is the first targeted therapy approved for the treatment of patients with HER2-mutant metastatic NSCLC, but the evidence in those with HER2 non-exon 19/20 mutations is scarce.MethodsWe reported treatment information and outcomes of four patients with metastatic NSCLC harboring HER2 non-exon 19/20 mutations who were treated with T-DXd.ResultsAll the four patients had metastatic lung adenocarcinoma and reached partial response to T-DXd treatment. A 57-year-old female patient with HER2 exon 17 V659E mutation received T-DXd as later-line treatment. Treatment was ongoing and the progression-free survival (PFS) had reached 13 months. Three patients received first-line T-DXd treatment. One patient with HER2 exon 3 T126A mutation had disease progression after 16-month treatment. The other two patients (one with HER2 exon 21 H878Y mutation and one with HER2 exon 17 V659E mutation) were continuing T-DXd treatment, both with a PFS of more than 6 months. No interstitial lung disease or grade ≥3 adverse events occurred in these four patients.ConclusionThe potential of T-DXd in patients with metastatic NSCLC harboring HER2 non-exon 19/20 mutations is considerable, which deserves to be validated in large-sample studies.